The interaction of gibberellin and melatonin promotes tobacco leaf growth and balances chemical components content in upper leaves - Xie, Haoran; Yu, Yufan; Yu, Shikang; Mu, Mingxin; Gu, Huizhan; Wang, Dong; Li, Junju; Liu, Xiaoli; Lu, Yifei; Ren, Bi; Lu, Liming; Li, Liqin (Frontiers in Plant Science, 2026)
IntroductionTobacco (Nicotiana tabacum L.) upper leaves constitute approximately one-third of total leaf production, yet their smaller leaf area, compact structure, and imbalanced chemical composition limit suitability for cigarette manufacturing. This study investigated whether gibberellin (GA) and melatonin (MT) could promote upper leaf growth and balance chemical components.MethodsA two-factor randomized block design experiment was conducted to evaluate GA and MT effects on tobacco upper leaves. Morphological parameters, biomass accumulation, and chemical composition were measured. Structural equation modeling and TOPSIS (Technique for Order Preference by Similarity to Ideal Solution) analysis were employed to determine regulatory pathways and optimal hormone combinations.ResultsGibberellin significantly promoted upper leaf morphological development. The 75 mg/L GA treatment increased leaf width and leaf area by 12.96% and 17.69%, respectively, and significantly enhanced both fresh and dry weight (P<0.01). The GA-MT interaction significantly increased biomass accumulation (P<0.05). Structural equation modeling indicated GA primarily drove dry matter accumulation through direct regulation of leaf area (path coefficient, 0.47) and fresh weight (path coefficient, 0.39). Single hormone treatments improved chemical quality, with Chemical Component Usability Index (CCUI) ameliorated under 80 μmol/L MT and 75 mg/L GA treatments. TOPSIS analysis identified 75 mg/L GA + 80 μmol/L MT as the optimal combination (closeness coefficient, 0.644), effectively balancing biomass increase with optimized chemical coordination.DiscussionThis study confirms gibberellin as the dominant factor regulating upper leaf morphology and biomass, while melatonin modulates chemical quality through interaction, providing a theoretical foundation and technical strategy for enhancing growth and chemical quality in tobacco upper leaves.